E-learning pills on immunotherapy in urothelial carcinoma: The E-PIMUC program for continuing medical education - Romero-Clarà, Olga; Madrid, Clara; Pardo, Juan Carlos; Ruiz de Porras, Vicenç; Etxaniz, Olatz; Moreno-Alonso, Deborah; Font, Albert (Frontiers in Pharmacology, 2024)
The high incidence and mortality rates of urothelial carcinoma mean it remains a significant global health concern. Its prevalence is notably pronounced in industrialized countries, with Spain registering one of the highest incidences in Europe. Treatment options are available for various stages of bladder cancer. Moreover, the management landscape for this disease has been significantly transformed by the rapid advances in immunotherapy. Healthcare professionals who diagnose, treat, and follow up with bladder cancer patients need comprehensive training to incorporate these advances into their clinical practice. To bridge these knowledge gaps, we set up the E-PIMUC program to educate healthcare professionals on bladder cancer management and specifically immunotherapy.Methods: E-PIMUC used an innovative microlearning methodology comprising bitesize learning pills that support efficient acquisition of specialized expertise. We used a mixed methods, quantitative and qualitative approach to assess the success of the E-PIMUC program. Data collection encompassed prepost testing, participation metrics, satisfaction surveys, and self-perceived performance assessments.Results: A total of 751 healthcare professionals enrolled in the program. Of these, 81.0% actively engaged with the content and 33.2% passed all tests and were awarded the course certificate and professional credits. The course received satisfaction ratings of 94.3% to 95.1% and significantly improved the declarative knowledge of participants who had a range of professional profiles (p<0.001). Participants reported increased confidence in applying immunotherapy principles in their practice (average improvement of 1.4 points). Open-ended responses also underscored participants' perceived benefits, including expanded knowledge and enhanced patient interaction skills.The E-PIMUC program provided effective, comprehensive, cutting-edge training on bladder cancer management, particularly on the use of immunotherapy in this area of oncology. The high participation rates, positive satisfaction scores, substantial knowledge enhancement, and improved self-perceived performance, are all testament to the program's success. E-PIMUC was endorsed by regulatory bodies as a trusted educational resource in urothelial carcinoma management. What is more, complementary initiatives brought together patients and medical experts to foster a holistic, patient-centered approach to the complexities of bladder cancer care.